First report in Peru on direct-acting antiviral therapy for chronic hepatitis C in HIV-positive patients - Collins, Jaime A. (2022)
Objective: To present the clinical experience with direct-acting antivirals (DAAs) for chronic hepatitis C in HIV-positive patients. Materials and methods: Longitudinal and prospective case series of HIV-positive patients treated with DAAs for chronic hepatitis C between May 2019 and April 2020 at the Infectious Diseases Service of Hospital G. Almenara, EsSalud. The primary outcome was sustained virologic response to hepatitis C virus (HCV) 12 weeks after completion of DAA therapy. Secondary outcomes were tolerability and safety. Results: Ten patients were included in the study, two were women (20%). Two patients had cirrhosis (20%). All patients had suppressed HIV viral load prior to DAA therapy. Patients received a 12-week regimen based on sofosbuvir: one with daclatasvir separately, and the remaining nine with velpatasvir combined in a single tablet per day. The sustained virological response of HCV was evaluable nine cases. In these, the HCV viral load was undetectable. No occurrences were recorded regarding tolerability and safety during therapy with the indicated DAAs. Conclusions: This present investigation is the first clinical experience in Peru with DAAs for chronic hepatitis C in HIV-positive patients. Virologic response, tolerability, and safety again njunction or in combination with sofosbuvir, were optimal in the case series presented.